Risk factors associated with myasthenia gravis in thymoma patients: The potential role of thymic germinal centers. Issue 106 (January 2020) - Lefeuvre, Claire MJ.; Payet, Cloé A.; Fayet, Odessa-Maud; Maillard, Solène; Truffault, Frédérique; Bondet, Vincent; Duffy, Darragh; de Montpreville, Vincent; Ghigna, Maria-Rosa; Fadel, Elie; Mansuet-Lupo, Audrey; Alifano, Marco; et al.
Abstract: Thymomas are associated with a very high risk of developing Myasthenia Gravis (MG). Our objectives were to identify histological and biological parameters to allow early diagnosis of thymoma patients susceptible to developing MG. We conducted a detailed retrospective analysis from a patient database, searching for differences between patients with thymoma-associated MG (MGT, n = 409) and thymoma without MG (TOMA, n = 111) in comparison with nonthymomatous MG patients (MG, n = 1246). We also performed multiplex and single molecule arrays to measure the serum levels of cytokines in these groups of patients and controls (n = 14–22). We identified a set of parameters associated with MG development in thymoma patients: 1) detection of anti-acetylcholine receptor (AChR) antibodies, 2) development of B1 or B2 thymoma subtypes, 3) presence of ectopic thymic germinal centers (GCs), 4) local invasiveness of thymoma, and 5) being a woman under 50 years old. Among these parameters, 58.8% of MGT patients displayed GCs with a positive correlation between the number of GCs and anti-AChR titers. By immunohistochemistry, we found thymic GCs in the adjacent tissues of thymomas encircled by high endothelial venules (HEVs) that could favor peripheral cell recruitment. We also clearly associated MG symptoms with higher IFN-γ, IL-1β and sCD40L serum levels, specifically in MGT patients compared to TOMA patients. Altogether, these analyses allowed the clear identification of histological, in particular the presence of GCs, and biological parameters that would facilitate the evaluation of the probability of the MG outcome postoperatively in thymoma patients. Highlights: Thymomas are associated with a very high risk to develop Myasthenia Gravis (MG). In thymoma, IFN-γ, IL-1β and sCD40L serum levels are linked to Myasthenia gravis. 60% of Myasthenia Gravis patients with thymoma display thymic ectopic germinal centers. Germinal centers in thymoma-associated MG are encircled by high endothelial venules. The thymus: tertiary lymphoid organ in thymoma-associated MG as in early-onset MG. Abstract : Disclosure: The authors report no disclosures relevant to the manuscript and have no conflict of interest.